GENERAL OVERVIEW ON EVOLUTION OF SOCIAL SERVICES FROM ROMANIA AND HUNEDOARA COUNTY IN THE SOCIO-ECONOMICAL CONTEXT OF POSTCOMMUNIST TRANSITION PERIOD (2000-2009) - FELICIA ANDRIONI (Annals of the University of Petrosani: Economics)
In the following, we make a general overview on social services provided by governmental and social institutions of NGOs in Romania and Hunedoara county in post-communist transition (2000-2009 period), before socio-economic crisis in Romania when the general trend was the development of social services. In this analyze used the following research methods: analysis documents, statistical analysis and comparative analysis.